Literature review : Biomimetic and conventional aircraft wing tips - Ahmed Siddiqui, Naseeb; Asrar, Waqar; Sulaeman, Erwin (Embry Riddle Aeronautical University, 2017)
This paper is an attempt to summarize the effect of wing tip devices employed by birds, as well as aeronautical engineers in the past to improve the performance characteristics of aircraft. The focus is on reduction of the induced drag or drag due to lift also known as inviscid drag. This paper will provide an insight on both biomimetic & conventional wing tip approaches to reduce the induced drag. Prior analysis and experiments on the aerodynamics of airplane performance due to both these separate studies have been discussed. The needs of the industry and their past inventions have been described briefly as well as new areas to be explored have been highlighted.